(untitled) (Global Journal of Management and Business Research, 2015)
The study was a content analysis of recently revised Malawian public accountancy curriculums with an aim of evaluating the level of ethics integration. The study also examined the old curriculums in order to appreciate the improvements that the revision made in relation to ethics integration. The study analysed the curriculums of three basic entry levels namely; certificate level, diploma level and degree level. The findings suggested that ethics was not integrated in the old certificate curriculum; however it is now embedded in a single course in revised curriculum. On the other hand, in both the old diploma and old degree curriculums, ethics was embedded only in auditing courses. However in the revised diploma curriculum, ethics is embedded in three additional courses. In the revised degree curriculum ethics is embedded in five additional modules, besides, a standalone module has been introduced. Thus the results suggest significant improvements in the level of ethics integration in the Malawian public accountancy education. The study recommends further comparative studies to evaluate the quality of integration, besides examining the efficacy of teaching, learning and assessment of ethics.